EFFECT OF SUSTAINABILITY REPORTING ON SHARE PRICES OF LISTED FINANCIAL FIRMS IN NIGERIA - MUSA, HASSAN; ALHASSAN, ABDULKARIM SHAIBU; MANTA, HARUNA MUSA (JOURNAL OF ECONOMICS AND ALLIED RESEARCH, 2025)
This study examines the effect of sustainability reporting specifically environmental, social, and governance (ESG) disclosures on the share prices of listed financial firms in Nigeria. The study focuses on firms listed on the Nigerian Exchange Group (NGX) over the period from 2014 to 2023. Adopting a longitudinal research design, data were collected from 47 financial firms that consistently disclosed sustainability reports for at least three consecutive years within the study period. Panel regression analysis was employed as the technique of data analysis. The findings reveal that both environmental and governance disclosures have a significant and positive effect on the share prices of listed financial firms. However, social disclosures were found to have an insignificant impact on share prices. Additionally, firm size exhibited a strong positive influence on share prices, suggesting that larger firms enjoy greater investor confidence and market valuation. The study concludes that enhanced sustainability reporting, particularly in environmental and governance areas, contributes to increased firm value in the Nigerian financial sector. It recommends that financial firms improve the quality and consistency of their sustainability disclosures and that regulatory bodies strengthen guidelines and enforcement to promote transparency and investor confidence.